What dreams may come - Ward, Vincent; Simon, Stephen, 1946-; Bain, Barnet; Bass, Ronald; Williams, Robin, 1952 July 21-; Gooding, Cuba, 1968-; Sciorra, Annabella; Sydow, Max von, 1929-; Grant, Jessica Brooks; Paddock, Josh.; Chao, Rosalind; Kamen, Michael; et al. (Polygram Video : Universal Studios [distributor, 2002)
Four years after Chris and Annie Nielsen lose their children in a traffic accident, Chris himself is killed and finds himself reunited with his children in a beautiful and astonishing afterlife, but Annie commits suicide in despair and is banished to a very different realm. Chris risks his own eternal happiness to find Annie and rescue her from her fate.
Based on the novel by Richard Matheson.
Originally released as motion picture in 1998.
THX digitally mastered.
Special features include director's commentary, 2 theatrical trailers, "making of" featurette, visual effects notes and clips, alternate ending, photo gallery, biographies and filmographies of featured cast and crew, Dreams desktop (Windows 95/98 and Macintosh).
Director of photography, Eduardo Serra ; cameras, Anastas M. Michos, Kim Marks ; steadicam operator, Mark R. Van Loon ; underwater photography, Rexford Metz ; still photographers, Frank Masi, Phil Bray ; editors, David Brenner, Maysie Hoy ; music, Michael Kamen.
Robin Williams, Cuba Gooding, Jr., Annabella Sciorra, Max von Sydow, Jessica Brooks Grant, Josh Paddock, Rosalind Chao.
Keywords: Man-woman relationships -- Drama; Future life -- Drama; Feature films